PERAN FILM SEBAGAI MEDIA SOSIALISASI LINGKUNGAN - Ahmad Toni (Universitas Muhammadiyah Yogyakarta, 2015)
Movies in international relations can not be separated from the imaging of a country to realize the access to information can influence people, groups and other countries in instilling the ideology and interests. As the theme of the film in general is holding on to the genre standard, the Asian Development Bank as a lending institution to fund the development of lagging countries and developing countries start and courage in carrying the theme of environment and sustainability, especially the availability of clean water.Keywords: Movie, Theme, Environment, Water.